Effect of GABA Application on the Growth and Yield of Bitter Gourd (Momordica charantia) - Md. Ashrafuzzaman; Ismail, Mohd Razi; Abdullah Ibna Fazal, K. M.; Uddin, Md Kamal; Prodhan, A. K. M. A. (2010)
An experiment was conducted to investigate the effect of GABA (GA3 1% & SBA Brassicasteroids as STC 0.3%) application on growth, yield and yield contributing traits of bitter gourd. GABA was applied at 0.5, 1.0, 1.5 and 2.0 mg L-1 as foliar spray at 30 days after sowing, while control plants received no GABA. The experiment was laid out in a randomized complete block design (RCBD) with four replications. Result showed that GABA had positive regulatory effect on morphological growth, yield and yield related traits of bitter gourd; nonetheless GABA application at 1.5 mg L-1 was found the most effective in improving length and diameter of main vine, individual branch length, number of branches, total branch length, number of nodes per plant, vine diameter, days to first male and female flowering, numbers of male and female flower, number of fruit, weight of individual fruit, length and diameter of fruit, percentage of fruit set and number of seeds per fruit. Hence GABA application at 1.5 mg L-1 as foliar spray could be the suitable concentration for enhancing growth and yield of bitter gourd.